Analisis Penerapan PSAK 101 pada Penyajian Laporan Keuangan Koperasi Syariah BMT Itqan - Intan Oktaviani; Cepi Saepuloh (MES Management Journal, 2024)
Baitul Maal Wa Tamwil (BMT) is a sharia-based cooperative, so sharia accounting principles must be applied in presenting its financial reports. This principle is based on the Statement of Sharia Financial Accounting Standards (PSAK) No. 101 concerning the Presentation of Sharia Financial Reports. The presentation of financial reports in accordance with PSAK 101 consists of 7 complete financial reporting components, including: balance sheet, profit and loss report, cash flow report, change report equity, reports on sources and utilization of zakat funds, reports on sources of use of charity funds, and notes to financial reports. This research aims to analyze and determine the application of financial report presentation in one of the 1,351 cooperatives in the city of Bandung, namely the BMT itQan Sharia Cooperative. The research method used to research this research is a descriptive research method with a qualitative approach. The techniques used in this research are observation, interviews and documentation using data analysis methods, data reduction, data presentation, as well as conclusions and verification. The results of this research conclude that there are several mandatory financial reports such as the financial position report, profit and loss report and change in equity report that are not in accordance with PSAK 101. For reports on the source and distribution of zakat funds, reports on the source and use of benevolent funds are made separately. in the Baitul Maal division so that it does not become a perfect series of financial report presentations. The cash flow statement is appropriate, and notes to the financial statements have not been made.